Unravelling direct and indirect effects of river-floodplain connectivity on biodiversity: insights from the Elbe River floodplains - Franziska Wenskus; Christian Hecht; Peter Horchler; Kathrin Januschke; Georg Rieland; Mathias Scholz; Arnd Weber; Daniel Hering (Biodiversity and Conservation, 2025)
River-floodplain connectivity is a critical ecological process influencing biodiversity and ecosystem functions. However, the impact of changes in this connectivity, particularly its loss, on biodiversity in floodplains remains insufficiently studied. This study aimed to assess how connectivity influences biodiversity metrics and whether it directly affects biodiversity indices for selected species groups, beyond its indirect influence through environmental variables. We used structural equation modelling to separate the direct effects of connectivity on plant and carabid beetle diversity from indirect effects mediated by flooding regimes, soil properties, and pollution in the Elbe River floodplains. We compared results from connected and decoupled floodplain sections to understand how these relationships change when connectivity is lost. Connectivity showed significant direct effects on most biodiversity metrics for both plants and carabids. For carabids, higher connectivity was associated with lower species richness and higher proportions of indicator species for wet grasslands, independent of intermediate factors such as flooding or soil conditions. For plants, higher connectivity was associated with higher species and functional richness, though only through indirect effects. Overall, connectivity had a positive impact on biodiversity, fostering higher species and functional diversity without leading to highly specialised, species-poor communities. Additionally, the models were largely consistent between connected and decoupled floodplains, suggesting that decoupling does not fundamentally alter the ecological mechanisms governing biodiversity, and that recovery through restoration is possible. Our findings highlight the complex role of river-floodplain connectivity in shaping floodplain biodiversity. Maintaining and restoring this connectivity is essential for promoting diverse and resilient floodplain ecosystems.